Produção biotecnológica de exopolissacarídeo por meio de conversão químico-fermentativa de casca de arroz - Pedroso, Giovanni Bressiani (2018)
The rice husk (RH) conversion in products with industrial and pharmaco-chemical attention aimed to use this raw lignocellulosic material, renewable and abundant in the south of Brazil, mainly at RS state ─ yet with no commercial value. The main goal was the production of exopolysaccharides (EPS) and, secondarily, to contribute to mitigate the improper disposal of this waste of processing. For this, the RH was submitted to alkaline pretreatment (KOH, Ca(OH)2, NaOH, CaCO3 and NH4OH) and/or by ozonation, followed by acidic pressurized (between 10 – 40 bar) hydrolysis with H2SO4, HCl, HNO3 and H3PO4, according to multivariate statistical design, using a central rotational compound design. The hydrolytical step was evaluated in three different configurations: a system consisting in a heating block (Berghof), a normal lab stove and a lab microwave oven. The hydrolytic experiments in heating block showed the best result at 135 °C and 55 min of reaction, with 4.9% (v v -1) H3PO4, producing 20.9 g L-1 of sugar (yield of 209.4 mg g-1 RH). Employing 2.5% (v v -1) H2SO4, 145 °C and 45 min of reaction, it was produced 16.1 g L-1 of sugar, yield of 161.5 mg g-1 RH in the best experiment with lab stove. Using a microwave oven, the better experiment yielded 15.3 g L-1 of sugar (yield 152.6 mg g-1 RH), using 1.5% (v v-1) HCl 135 °C and 55 min of reaction. Regarding the results, it is possible to distinguish the action profile of each acid over the RH: H2SO4 or HCl mainly release glucose as HNO3 or H3PO4 generate better xylose yields. The best results of the alkaline hydrolysis were 21.7 g L-1, yield increase of 51% by using KOH (65 ° C, 60 min, alkali at 4.25% m v-1), 24.0 g L-1, yield increase of 66% with NaOH (65 ° C, 35 min, alkali at 4.25% m v-1). The use of ozonation, on the other hand, besides its character residue-free, resulted in productivities of 16.1 g L-1 (yield rise of 11%). Previous fermentative experiments for the growth of the bacterium Rhizobium radiobacter (LMG196 and ATCC4720) in the RH hydrolysate were successful. A multivariate design evaluated the culture conditions (10% inoculums volume (1x109 UFC mL-1), pH 7.0, 100 rpm, 72 h) and yeast extract supplementation (9.0 g L-1), KH2PO4 (1.0 g L-1) and FeSO4. Under these conditions it is possible to produce extractable EPS (by using cooled isopropanol) with yields of 69.0 g L-1 (41.6 g 100 g-1 CA), significant value from 72 h culture growth (with sulfuric hydrolysate detoxified with 4.0% m v-1 active carbon). The analytical techniques used were liquid chromatography, HPLC-RID and HPLC-DAD, and UV-vis spectrophotometry, discussing the figures-of-merit and validation methodologies developed. For the product characterization it was used the analytical techniques of NMR 1H, FT-IR and GPC. It was demonstrated the viability of the fermentable sugar production process from the RH, on a laboratory scale and, also, the feasibility of its bioconversion in EPS (purity of 91.2%), which contributes markedly to the effort of the development of biotechnology research and scientific innovation.